Does blending the ashes of chestnut shell and lignite create synergistic interaction on ash fusion temperatures? - Haykiri-Acma, H.; Yaman, S.; Kucukbayrak, S.; Morcali, M.H. (Elsevier BV, 2015)
Abstract The ashes of twelve different Turkish lignites were blended with the ash of chestnut shell (20 wt.%) to investigate the effects of the biomass ash on the ash fusion temperatures (AFTs) of the ashes of coal/biomass blends. Fusion characteristics of ashes were studied according to ASTM D1857. Calculated values (theoretical values) of AFTs were compared with the experimental ones to evaluate the existence of additive behavior or synergistic/antagonistic interactions between the ashes. It was found that the presence of the ash of chestnut shell led to more or less lowering trends in AFTs in eleven of the twelve lignite ashes and this is an undesirable interaction. Although, the chestnut shell contains high amount of Ca, it was concluded that the improving effect of Ca on ash fusion temperatures are overtaken by the lowering effect of K. Alumina-silicate minerals in lignite ashes may show interaction with K to form new phases with low melting temperatures. Consequently, it was found out that the increasing acidic oxides (SiO 2  + Al 2 O 3  + TiO 2 ) in ash leads to high levels of deviations from the calculated values (additive behavior) of AFTs and particularly the Al content is the key parameter.